The Influence of Feedback Environment towards Teacher’s Career Adaptability among Primary School Teachers in Kuching - Ling, Ying-Leh; Cheng Gek, Grace Kho (Online Journal for TVET Practitioners, 2020)
Prolonged stress can cause teachers to have a bad impact on students and their teaching. This will make teachers lose their ability to teach. These problems will indirectly affect the teacher's career adaptability. This study intended to determine the significant relationship between feedback environment and career adaptability among Primary School teachers in Kuching. There were 76 respondents randomly selected to participate in this study. Data were collected using the questionnaire. Pearson correlation and multiple linear regression analysis techniques were used to analyze the data collected. The results show that feedback credibility, quality feedback, favorable feedback, and feedback seeking behavior have a positive and significant relationship with the dimension of career adaptability which includes career concern, career control, career curiosity and career confidence. The findings have shown feedback delivery and feedback availability do not have a significant relationship with all the dimensions of career adaptability. The study further identified that the significant effect of career adaptability. The results found that there is a significant relationship between the two significant predictor variables (feedback credibility and feedback quality) with career adaptability. The analysis results have shown that the combination model of feedback credibility and feedback quality appears to be significant toward career adaptability among the teachers. Thus, the study concludes that there is a significant relationship between feedback environment and career adaptability and on the other hand feedback credibility and feedback quality has a significant influence on career adaptability. The findings of this study indicate that there is a need for top management to create a feedback environment in career adaptability by emphasizing the credibility and quality of individuals in delivering the feedback in their work organization.